2021
DOI: 10.2147/oaem.s297083
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Study on Acute Poisoning Cases Brought for Medico-Legal Autopsy in a North-Eastern City of India

Abstract: Purpose Death due to acute poisoning is one of the significant health challenges to cope-up. It is imperative to know the death victims’ pattern due to acute poisoning to prepare the relevant preventive and remedial measures. Therefore, the present study aimed to assess the pattern of the dead victims of acute poisoning in a tertiary care centre. Materials and Methods It is a hospital record-based study and conducted in a tertiary care centre. Descriptive statistics to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The difference might be due to the different study setting, and low training in this study population ( Tesfaye et al, 2014 ). For example, in this study setting, nearly 51% of nurses were not trained in the management of patients with acute poisoning, whereas Goswami et al (2021 ) study found that 65% of nurses were trained.…”
Section: Discussionmentioning
confidence: 60%
“…The difference might be due to the different study setting, and low training in this study population ( Tesfaye et al, 2014 ). For example, in this study setting, nearly 51% of nurses were not trained in the management of patients with acute poisoning, whereas Goswami et al (2021 ) study found that 65% of nurses were trained.…”
Section: Discussionmentioning
confidence: 60%
“…al. [8] The common reasons for consuming poison were Familial discord (21.4%) followed by financial matters 16.67%, and unemployment (15%) which corresponds to the findings observed in the studies conducted by S.K Dhattarwal et al, [9] and disagreement with Taruni Ng [10]. This is attributed to factors like failures in academics, romantic failure, family disputes, marital disharmony, unemployment, romantic failures, ill health, and dowry harassment in the case of females.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective study by Goswami et al [20] examined autopsies of suspected deaths by poisoning. Of the 584 cases, 41.8% (244) were of poisoning, of which, 86% (210) were cases of suicide.…”
Section: Asiamentioning
confidence: 99%